Geoedupreneurship Studies in Higher Education Geography Learning in Indonesia - Maghfiroh, Ainun; Sumarmi; Utaya, Sugeng; Wahyudi, Adip; Al Kindy, Muhammad Asyrofi; Nurjati, Radya Wirawan (Universitas Muhammadiyah Surakarta, 2026)
The transformation of higher education in Indonesia encourages the integration of entrepreneurial values into various disciplines, including geography education. Geoedupreneurship presents itself as an approach that combines spatial science and entrepreneurship based on local potential. This study aims to analyze the suitability of learning planning, the development of graduate learning outcomes, and the actual implementation of geoedupreneurship in higher education in Indonesia, with the higher education curriculum guidelines. A qualitative descriptive approach was used through analysis of Semester Learning Plan documents, student surveys, learning observations, and interviews. The results show that learning planning in geography education entrepreneurship courses at universities in Indonesia shows an average suitability of 81.43%, while the development of graduate learning outcomes achieves a level of alignment of 78% with the higher education curriculum guidelines. The implementation of a project-based approach supported by micro e-learning technology supports geoedupreneurship learning activities. However, 45.2% of students experience obstacles in integrating entrepreneurship concepts with geographical issues, and 54.8% state the need for contextual and applicable digital learning materials. The planning and implementation of geoedupreneurship are structured and adaptive, but require strengthening of learning instruments and the development of contextual digital learning materials. The geoedupreneurship approach has an important contribution in producing graduates with spatial competitiveness and entrepreneurship but requires further research to strengthen curriculum integration and the development of digital geoedupreneurship learning materials based on local potential that are oriented towards work competencies and support the achievement of geoedupreneurship learning objectives at the higher education level.